Mudança Ambiental Global e Segurança Humana - Rafael D'Almeida Martins (INTERthesis)
MATTHEW, R.A.; BARNETT, J.; MCDONALD, B.; O'BRIEN, K.L. (Eds). Global Environmental Change and Human Security. Massachusetts: MIT Press, 2010. 326 p.